Impact of Chronic Smoking on Choroidal Thickness: A Comparative Analysis Using Optical Coherence Tomography - Mazumdar, Ranabir; Maulik, Subhamitra; Wasim, Nazir Abdul (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Chronic smoking has systemic vascular effects, including alterations in ocular blood flow and choroidal thickness, impacting visual health.Objective: To compare choroidal thickness (CT) in chronic smokers and nonsmokers using optical coherence tomography and to evaluate the effect of smoking duration on CT based on pack-year quartiles (PYQ).Methods: This was a case-control study conducted at the Regional Institute of Ophthalmology, Medical College, Kolkata, India between January 2023 and June 2024. Choroidal thickness was assessed in 120 cases (60 smokers and 60 nonsmokers) over a period of 18 months. Choroidal thickness was measured using Enhanced Depth Imaging Spectral-Domain Optical Coherence Tomography (EDI SD-OCT) at the sub foveal region and 1.5 mm away in the superior, inferior, nasal, and temporal directions. CT between smokers and nonsmokers was compared. Statistical analysis was performed using the SPSS 23.0 software and a p-value of less than 0.05 was taken as statistically significant.Results: The study analyzed age distribution, ocular parameters, and choroidal thickness in 60 smokers and 60 nonsmokers. The mean age in smokers and nonsmokers was found to be 43.1 ± 7.2 and 40.8 ± 11.4 years respectively. Smokers were found to have a significantly lower sub foveal CT compared to nonsmokers (272.42 ± 13.57 µm vs. 284.94 ± 14.15 µm, p<0.05). Increased smoking exposure significantly correlated with progressive choroidal thinning (p<0.05). Other ocular parameters, such as intraocular pressure (p=0.235) and axial length (p=1.0), were found to be comparable in both groups (p>0.05).Conclusion: There significant choroidal thinning in chronic smokers as compared to nonsmokers with a dose-dependent effect linked to higher smoking exposure. These findings suggest a smoking-induced vascular compromise in the choroid.